2002
DOI: 10.1128/jcm.40.4.1333-1338.2002
|View full text |Cite
|
Sign up to set email alerts
|

rpoB Gene Sequence-Based Identification of Staphylococcu s Species

Abstract: The complete sequence of rpoB, the gene encoding the beta subunit of RNA polymerase was determined for Staphylococcus saccharolyticus, Staphylococcus lugdunensis, S taphylococcus caprae, and Staphylococcus intermedius and partial sequences were obtained for an additional 27 Staphylococcus species. The complete rpoB sequences varied in length from 3,452 to 3,845 bp and had a 36.8 to 39.2% GC content. The partial sequences had 71.6 to 93.6% interspecies homology and exhibited a 0.08 to 0.8% intraspecific diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
198
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(206 citation statements)
references
References 39 publications
6
198
1
1
Order By: Relevance
“…Species-level identification studies have often been based on sequencing of certain genes (Poyart et al, 2001;Drancourt & Raoult, 2002) and hybridization studies (Goh et al, 1997). In addition, PCR analyses of the length polymorphisms of the intergenic spacers residing between the 16S and 23S rRNA genes (Gurtler & Stanisich, 1996) or tRNA genes (Welsh & McClelland, 1992;Ehrenstein et al, 1996) have also been important targets for the species-level identification of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Species-level identification studies have often been based on sequencing of certain genes (Poyart et al, 2001;Drancourt & Raoult, 2002) and hybridization studies (Goh et al, 1997). In addition, PCR analyses of the length polymorphisms of the intergenic spacers residing between the 16S and 23S rRNA genes (Gurtler & Stanisich, 1996) or tRNA genes (Welsh & McClelland, 1992;Ehrenstein et al, 1996) have also been important targets for the species-level identification of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the use of 16S rDNA sequencing for taxonomic purposes, subtle sequence differences in the 16S rDNA sequence were recently reported to be useful for species identification [34,39] and for subtyping and identifying hyper-virulent bacterial clones [5,31,33]. For the same purposes, the rpoB gene encoding the β-subunit of RNA polymerase has been studied for many bacterial species, such as Bacillus [24], Bartonella [37], Borrelia [28], Legionella [25], Staphylococcus [14], mycobacteria [22] and enteric bacteria [32]. The rpoB sequences of H. somni strains have been determined and analysed phylogenetically [1] although sequence stretches or cluster groups corresponding to the host-specific subgroups were not clear due to the use of limited number of bacterial strains.…”
mentioning
confidence: 99%
“…In contrast to the probe hybridization technique and the RFLP approach, sequencing enables any isolate to be characterized, including new species by their phylogenetic relationships (Drancourt & Raoult 2002). And these authors concluded that the partial sequencing of the rpoB gene as a suitable new tool for the accurate identification of Staphylococcus isolates.…”
Section: Discussionmentioning
confidence: 99%